Qualitative and Quantitative Characteristics of Papillomavirus Infection in Women with Inflammatory and Neoplastic Processes of the Cervix - Isomadinova Guzal Zaxriddin qizi (Periodica Journal, 2022)
The purpose of the work is to establish the qualitative and quantitative laboratory characteristics of human papillomavirus infection (PVI) in women with inflammatory and neoplastic processes of the cervix.
Keywords: Laboratory; Quantitative; Infection; Papillomavirus